IDEA MANAGEMENT SYSTEM - AN ESSENTIAL COMPONENT IN THE CONTINUOUS IMPROVEMENT OF QUALITY AND INNOVATION - Santos, Gilberto (2016)
It is known the power of ideas is tremendous. But there are employees in many companies who have good ideas but not put them into practice. On the other hand, there are many others who have good ideas and are encouraged to contribute their ideas for innovation in the company. This study attempts to identify factors that contribute to success in managing ideas and consequent business innovation. The method used was the case study applied to two companies. During the investigation, factors considered essential for the success of an idea management program were identified, of which we highlight, among others, evidences the results, involvement of the top management, establishment of goals and objectives; recognition; dissemination of good results. Companies with these implemented systems, capture the best ideas from their collaborators and apply them internally. This study intends to contribute to business innovation in enterprises through creation and idea management, mainly through collecting the best ideas of their own employees. The results of this study can be used to help improving deployed suggestions systems, as well as, all managers who wish to implement suggestions systems/ideas management systems.